Effects of stretching training on pain severity and frequency of leg cramps in Middle-aged women with metabolic syndrome - Roghayyeh Gholizadeh; Ali Hasani; Hamid Arazi (Mashhad University of Medical Sciences, 2017)
Introduction: Leg cramp is associated with high levels of blood glucose, triglycerides, blood pressure, obesity and decreased HDL in middle-aged women that is associated with painful contractions, which leads to disorder of walking and health in the individual. Therefore, due to these disorders, this study was performed with aim to investigate the effects of calf muscles and hamstrings stretching training on pain severity and leg cramps in women with metabolic syndrome. Methods: This semi experimental study was performed by pretest-posttest with control group in 2015 on 24 patients with metabolic syndrome in Fouman city. After the measurement of leg cramps and metabolic syndrome variables, the subjects were randomly divided into two groups of experimental and control. Stretching training was performed for 6 weeks, 5 days per week for 45 to 50 minutes. The intensity and frequency of leg cramps were assessed by visual analogue scale. Data was analyzed by SPSS software (version 20) and dependent t test and covariance analysis. P<0.05 was considered significant. Results: Stretching training significantly reduced the intensity and frequency of leg cramps (p<0.05); while the changes of pain severity was not significant between two groups (p>0.05). Also, the changes of metabolic syndrome indices and anthropometric measurements before and after training was not significant the experimental group (p>0.05). Conclusion: 6 weeks of stretching training can affect the leg muscles cramps and so can be useful in improving of leg cramps indices (intensity of frequency). Therefore, according to the results, women with metabolic syndrome can use stretching training for possible prevention of leg muscles cramps disorders and reducing its complications in daily life.